Personal relations and social media: The emotional experience on Instagram - Pantalos, Emmanouil; Katsimigas, Lampros; Komninou, Athina; Makrysopoulou, Panagiota (Homo Virtualis, 2022)
Social network sites such as Facebook and Instagram have become an online venue where people nowadays form and maintain relationships, socialize and exchange social or other information. This study explores the Instagram experience and its effects on feelings, anxiety and a series of other related variables. Results of the self-report quantitative correlative method (n=289) revealed indifference as the primary feeling associated with Instagram use in general, slightly surpassed by happiness, love and pride only in cases when Instagram use was positively personalized. Regarding Instagram anxiety, results showed no sex differences, a negative correlation with age and a positive correlation with amount of use. Instagram anxiety was also found to correlate with social comparison, passive and active use as well as social presence, indicating that content and type of involvement is likely to have emotional and psychological effects. A high correlation was found between Instagram anxiety and problematic use. Self-esteem was found to correlate negatively with Instagram anxiety. A positive relationship was found between social comparison and use, active or passive. Finally, the number of users one follows was found to play a role in the amount of Instagram anxiety.